Improving Quality of Teachers: Why and How? - Sahni, Madhu (JOURNAL OF INDIAN EDUCATION, 2011)
Teacher quality plays a critical role in affecting student’s performance. Not only do policy makers hold students to high standards, but they have elevated their expectations for teacher standards also. Emphasising teacher educators have much to contribute to the development of quality amongst the teachers; the author offers suggestions for improving quality of teachers.